Climate model ensemble data for Neoproterozoic Snowball-Earth inceptions - placeholder - Eberhard, Julius; Bevan, Oliver E.; Feulner, Georg; Petri, Stefan; van Hunen, Jeroen; Baldini, James U. L. (GFZ Data Services, 2023)
Abstract The Cryogenian period (720--635~million years ago) in the Neoproterozoic era featured two phases of global or near-global ice cover, termed `Snowball Earth'. Here we present a comprehensive sensitivity study considering different scenarios for the Cryogenian continental configuration, orbital geometry, and short-term volcanic cooling effects in a consistent model framework, using the climate model of intermediate complexity CLIMBER-3α. The continental configurations comprise palaeogeography reconstructions for both Snowball-Earth periods from two different sources, as well as two idealised configurations with either uniformly dispersed continents or a single polar supercontinent. Orbital geometries are sampled as multiple different combinations of the parameters obliquity, eccentricity, and argument of perihelion. For volcanic eruptions, we differentiate between single globally homogeneous perturbations, single zonally resolved perturbations, and random sequences of globally homogeneous perturbations with realistic statistics. The CO2 threshold lies between 10 and 250 ppm for all simulations. Methods We use the relatively fast intermediate-complexity model CLIMBER-3α to be able to run a large number of simulations. CLIMBER-3α consists of (1) an improved version of the ocean general circulation model MOM3 run at a coarse horizontal resolution of 3.75 x 3.75 degrees with 24 vertical layers, (2) the sea-ice model ISIS operated at the same horizontal resolution and capturing both the thermodynamics and dynamics of sea ice, and (3) the fast statistical--dynamical atmosphere model POTSDAM-2 with grid cells measuring 22.5 degrees in longitude and 7.5 degrees in latitude. The main limitations of the model relate to its simplified atmosphere component. For more details see the corresponding article.